2020
DOI: 10.1002/jhbp.796
|View full text |Cite
|
Sign up to set email alerts
|

New metastasectomy criteria for peritoneal metastasis of hepatocellular carcinoma: A study of the Japanese Society of Hepato‐Biliary‐Pancreatic Surgery

Abstract: Among extrahepatic metastases of hepatocellular carcinoma (HCC), the incidence rate of peritoneal metastasis (6%-11%) is much lower than the lung, bone, lymph node, or adrenal gland metastasis rates. 1,2 HCC larger than 5 cm, the presence of vascular invasion, a positive resection margin, poorly differentiated HCC, and radiofrequency ablation on HCC near the liver surface are considered to be risk factors for peritoneal metastasis. 3,4 HCC treatment guidelines in Japan recommend systemic chemotherapy, that is,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The 5-year OS rate of patients with an abdominal cancer index (PCI) ≤6 and no residual tumor was 43%, and their prognosis was much better than that of patients who did not meet those criteria. 18 In this study, the median survival time of the 15 patients was 18.6 months, and the median DFS time was 6.5 months. Among these patients, 3 had a DFS of more than 5 years.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The 5-year OS rate of patients with an abdominal cancer index (PCI) ≤6 and no residual tumor was 43%, and their prognosis was much better than that of patients who did not meet those criteria. 18 In this study, the median survival time of the 15 patients was 18.6 months, and the median DFS time was 6.5 months. Among these patients, 3 had a DFS of more than 5 years.…”
Section: Discussionmentioning
confidence: 59%
“…The 5-year OS rate of patients with an abdominal cancer index (PCI) ≤6 and no residual tumor was 43%, and their prognosis was much better than that of patients who did not meet those criteria. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Statistically, approximately 7-7.6% of patients with peritoneal metastasis were found to have reoperation ( 23 , 24 ), which was similar to our results (6.3% of patients with peritoneal metastases during reoperation). Evidently, the poor prognosis association with peritoneal metastasis has also been demonstrated in multiple abdominal cancers, such as colorectal, gastric and liver cancers ( 25 27 ).…”
Section: Discussionmentioning
confidence: 95%
“…Recently, systemic treatments for HCC have advanced [ 11 , 12 ] and can be used for patients with extrahepatic lesions [ 4 , 5 , 11 , 12 , 13 ]. However, some reports have suggested that the resection of a disseminated tumor may have beneficial effects on the prognosis [ 14 , 15 , 16 ]. Some studies have also suggested the clinical utility of cytoreductive surgery in combination with other therapies [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%